Adaptasi dan Keragaan Hasil Varietas Unggul Padi di Lahan Rawa Wilayah Perbatasan Kalimantan Barat - Koesrini, Koesrini; Alwi, Muhammad; Saleh, Muhammad (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2019)
Farmers cultivated rice once a year during the rainy season uses Cilosari variety with low yield (2.35 t/ha) in Matang Danau Village, Paloh Sub District, Sambas District, West Kalimantan Province. Increasing cropping index could be done by water pumping in dry season planting and using high yield adaptable varieties. The purpose of this research was to evaluate the adaptability and performance yield of highly rice variety in swamp lands West Kalimantan Border Area. The field experiment was carried out in Matang Danau village, Paloh Sub District, Sambas District, West Kalimantan Province, in the dry season from Maret to July 2018 and in the wet season from Oktober 2018 to February 2019. The research was arranged in randomized completely block design, with 3 replicates. The varieties tested, i.e., Inpara 1, 2, 3, 4, 6, 8, 9, Inpari 32, and check varieties Margasari and Cilosari. The results of the varieties adaptation test showed that there were differences in adaptation of varieties tested in swamps. Based on the results of the Inpara 1 variety, the highest yield was 6.6 t/ha, while the other varieties produced between 3.98-5.90 t/ha. The highest increasing yield compared to the varieties Margasari and Cilosari, i.e. Inpara 1. The increasing yield of rice in rainy season planting was higher 89,4% than that of the dry season.